2018
DOI: 10.1038/s41598-018-26841-3
|View full text |Cite
|
Sign up to set email alerts
|

Screening and characterisation of sex differentiation-related long non-coding RNAs in Chinese soft-shell turtle (Pelodiscus sinensis)

Abstract: Long non-coding RNAs (lncRNAs) perform distinct functions in various biological processes in mammals, including sex differentiation. However, the roles of lncRNAs in other vertebrates, especially in the Chinese soft-shell turtle (Pelodiscus sinensis), remain to be clarified. In this study, we performed genome-wide analysis of the lncRNA expression profiles in gonad tissues and screened numerous sex-specific lncRNAs in the Chinese soft-shell turtle. Of the 363,310,650 clean reads obtained, 5,994 sequences were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 59 publications
0
29
0
Order By: Relevance
“…However, their exact functions in the soft-shelled turtle remain poorly understood. Despite limited studies that have identi ed lncRNAs in the turtle [3], the miRNAs and lncRNAs in the database are still insu cient. In the present study, to understand the molecular mechanism involved in the reproduction of P. sinensis, we analysed the genome-wide expression of miRNAs, lncRNAs, and mRNAs in the mature ovaries and testes during the reproductive season.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, their exact functions in the soft-shelled turtle remain poorly understood. Despite limited studies that have identi ed lncRNAs in the turtle [3], the miRNAs and lncRNAs in the database are still insu cient. In the present study, to understand the molecular mechanism involved in the reproduction of P. sinensis, we analysed the genome-wide expression of miRNAs, lncRNAs, and mRNAs in the mature ovaries and testes during the reproductive season.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, Huang et al [32] identi ed only 10 miRNAs in P. sinensis based on EST and GSS information using a bioinformatics approach. Zhang et al [3] identi ed 5 994 lncRNAs by high-throughput sequencing in juvenile turtle gonads. MiRNAs and lncRNAs have been shown to have stage-speci c expression in animals [16,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have shown that lncRNA participate in many biological processes, such as sexual reproduction (Zhang et al, 2014), gonadal development (Taylor et al, 2015), and gametogenesis (Herrera et al, 2005;Laiho et al, 2013). Bioinformatic analysis of Amur sturgeon (Zhang et al, 2019) and Chinese softshell turtle (Zhang et al, 2018) gonads have shown that the expression of the majority of lncRNAs is signi cantly different between males and females. Target genes prediction has shown lncRNAs could regulate many genes responsible for sex determination and gametogenesis (Wen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, their exact functions in the soft-shelled turtle remain poorly understood. Despite limited studies that have identified lncRNAs in the turtle[3], the miRNAs and lncRNAs in the database are still insufficient. In the present study, to understand the molecular mechanism involved in the reproduction of P. sinensis, we analyzed a genome-wide expression of miRNAs, lncRNAs, and mRNAs in the mature ovaries and testes during the reproduction season.…”
mentioning
confidence: 99%